Outcomes with empagliflozin in heart failure with preserved ejection fraction using DELIVER-like endpoint definitions - Anker, Stefan; Siddiqi, Tariq Jamal; Filippatos, Gerasimos; Zannad, Faiez; Ferreira, João Pedro; Pocock, Stuart J.; Brückmann, Martina; Zeller, Cordula; Packer, Milton; Butler, Javed (European journal of heart failure, 2022)
Aims To report data from EMPEROR-Preserved according to prespecified endpoints of DELIVER. Methods and results In order to assess the impact of DELIVER-like definition on EMPEROR-Preserved outcomes, the following differences were reconciled: (1) the primary outcome in DELIVER added urgent heart failure (HF) visits to cardiovascular death or HF hospitalizations; (2) the EMPEROR-Preserved trial did not require documentation of physical findings or laboratory tests for confirming a HF hospitalization and it included events of 12-24 h if intensification of treatment was not only oral diuretics; (3) DELIVER excluded undetermined causes of deaths from the primary endpoint; (4) the composite renal endpoint in DELIVER included a sustained ≥50% decline in estimated glomerular filtration rate and incorporated renal death; and (5) DELIVER will assess outcomes in the overall population and in patients with ejection fraction (EF) <60% separately. Using the endpoint definitions from DELIVER, the primary outcome overall occurred in 13.1% in the empagliflozin and 16.8% in the placebo group (hazard ratio [HR] 0.76, 95% confidence interval [CI] 0.67-0.87; p < 0.0001). The relative risk reduction (RRR) changed from 21% to 24% when urgent HF visits were added, and undetermined death was eliminated. Compared to overall population RRR of 24%, it was 28% in patients with EF <60%. Death from cardiovascular causes excluding undetermined causes occurred in 6.2% in the empagliflozin and in 7.1% in the placebo group (HR 0.88, 95% CI 0.73-1.07). The RRR for the composite renal endpoint changed from 22% in the overall population (HR 0.78, 95% CI 0.54-1.13) to 40% when patients with EF <60% were assessed (p = 0.037). Conclusion Findings from EMPEROR-Preserved were modestly altered when analysed using cardiovascular trial endpoint definitions of the DELIVER trial. For the composite renal endpoint, the effect of empagliflozin became statistically significant in patients with EF <60% using the DELIVER definition.